2024
DOI: 10.1101/2024.01.16.24301337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antiviral efficacy of fluoxetine in early symptomatic COVID-19: an open-label, randomised, controlled, adaptive platform trial (PLATCOV)

Podjanee Jittamala,
Simon Boyd,
William HK Schilling
et al.

Abstract: Background The selective serotonin reuptake inhibitors (SSRIs) fluoxetine and fluvoxamine were repurposed for the treatment of early COVID-19 based on their antiviral activity in vitro, and observational and clinical trial evidence suggesting they prevented progression to severe disease. However, these SSRIs have not been recommended in guidelines and their antiviral activity in vivo has not been characterised. Methods PLATCOV is an open-label, multicentre, phase 2, randomised, controlled, adaptive pharmacomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Randomized clinical trials and retrospective studies have already demonstrated that treatment with antidepressants result in a milder course of COVID-19 and a reduced mortality rate [ 20 , 23 , 47 , 48 , 49 , 50 ]. Furthermore, there was a lower infection rate among patients using antidepressants, indicating that fluoxetine and sertraline may have a protective effect against SARS-CoV-2 infections [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials and retrospective studies have already demonstrated that treatment with antidepressants result in a milder course of COVID-19 and a reduced mortality rate [ 20 , 23 , 47 , 48 , 49 , 50 ]. Furthermore, there was a lower infection rate among patients using antidepressants, indicating that fluoxetine and sertraline may have a protective effect against SARS-CoV-2 infections [ 51 ].…”
Section: Discussionmentioning
confidence: 99%